Shark attacks on the Transkei Coast of South Africa: A case report - Banwari L. Meel (AOSIS, 2009)
Shark attacks are relatively uncommon, but can be fatal in nature. It is diffcult to understand the behaviour and motivation of this predator. In the summer of 1998 a 28-year-old male, who was an experienced, enthusiastic surfer, was attacked by a shark near Hole-in-the Wall on the Wild Coast in the Transkei region of South Africa. His right lower limb was severed, with profuse bleeding from the torn femoral artery. Sharp broken ends of the femur and torn muscles were noticed at autopsy. The viscera were extremely pale. The lungs, in addition to being pale, were shrunken and dry, and there was no fluid that oozed out upon squeezing the cut surface. The case history, physical findings, and medico-legal implications are discussed in this report. Preventive and safety measures related to shark attacks are suggested.